Uncovering the Circular Polarization Potential of Chiral Photonic Cellulose Films for Photonic Applications - Zheng, Hongzhi; Li, Wanru; Li, Wen; Wang, Xiaojun; Tang, Zhiyong; Zhang, Sean Xiao‐An; Xu, Yan (Advanced materials (Weinheim), 2018)
Circularly polarized light (CPL) is central to photonic technologies. A key challenge lies in developing a general route for generation of CPL with tailored chiroptical activity using low‐cost raw materials suitable for scale‐up. This study presents that cellulose films with photonic bandgaps (PBG) and left‐handed helical sense have an intrinsic ability for circular polarization leading to PBG‐based CPL with extraordinary |g | values, well‐defiend handedness, and tailorable wavelength by the PBG change. Using such cellulose films, incident light ranging from near‐UV to near‐IR can be transformed to passive L‐CPL and R‐CPL with viewing‐side‐dependent handedness and |g | values up to 0.87, and spontaneous emission transformed to R‐CPL emission with |g | values up to 0.68. Unprecedented evidence is presented with theoretical underpinning that the PBG effect can stimulate the R‐CPL emission. The potential of cellulose‐based CPL films for polarization‐based encryption is illustrated. The evaporation‐induced self‐assembly coupled with nanoscale mesogens of cellulose nanocrystals opens new venues for technological advances and enables a versatile strategy for rational design and scalable manufacturing of organic and inorganic CPL films for photonic applications. Chiral photonic cellulose films have intrinsic ability to generate and manipulate circularly polarized light (CPL) with extraordinary |g | values in a broad spectral regime. The CPL handedness is well defined, and the wavelength control is simple to realize. Photonic bandgap effects cause stimulated CPL. It presents a versatile and scalable strategy for customized CPL materials using renewable cellulose for photonic applications.